2015
DOI: 10.3390/ijms160511659
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity-Supported Chronic Toxicity Prediction: A k-Nearest Neighbor Coupled Read-Across Strategy

Abstract: A k-nearest neighbor (k-NN) classification model was constructed for 118 RDT NEDO (Repeated Dose Toxicity New Energy and industrial technology Development Organization; currently known as the Hazard Evaluation Support System (HESS)) database chemicals, employing two acute toxicity (LD50)-based classes as a response and using a series of eight PaDEL software-derived fingerprints as predictor variables. A model developed using Estate type fingerprints correctly predicted the LD50 classes for 70 of 94 training se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…By comparing their performances, it was found that RF usually outperformed [ 91 ]. Using the k-NN algorithm, Chavan et al even tried to predict the chronic toxicity of chemical substances by combining acute toxicity information with molecular fingerprints such as MACCS and CDK [ 93 ]. These studies demonstrated that chemical properties can help improve accuracy of toxicity prediction.…”
Section: Chemical Structure Descriptorsmentioning
confidence: 99%
“…By comparing their performances, it was found that RF usually outperformed [ 91 ]. Using the k-NN algorithm, Chavan et al even tried to predict the chronic toxicity of chemical substances by combining acute toxicity information with molecular fingerprints such as MACCS and CDK [ 93 ]. These studies demonstrated that chemical properties can help improve accuracy of toxicity prediction.…”
Section: Chemical Structure Descriptorsmentioning
confidence: 99%
“…To predict oral acute toxicity (LD50), regression models are developed with a confined applicability domain to improve prediction accuracy 1,4 . Chavan et al used k-Nearest Neighbor (KNN) method to predict the acute toxicity of chemicals with 79.17% accuracy 5 . Cherkasov et al predicted the antibacterial activity of chemicals with 93% accuracy using the Artificial Neural Network (ANN) method for Quantitative Structure-Activity Relationship (QSAR) model 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of open source fingerprints, such as PaDEL fingerprints, which are libraries of descriptors [ 24 ], allows for ready access to tools for predicting biological endpoints. A recent report on the use of PaDEL fingerprints in conjunction with a k -NN strategy aimed at the prediction of chronic toxicity [ 25 ] prompted us to apply this approach to hERG-channel blockers, a far more focused system. It was envisaged that publicly available data on a series of hERG-channel blockers could function as a starting point for model construction, and a series of 1953 PubChem compounds could act as basis for validation.…”
Section: Introductionmentioning
confidence: 99%